EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMK NEGERI 10 MERANGIN - Nurul Hikmah; Ferinaldi; Sugeng Riyadi (Hira Institute, 2025)
This inquire about points to depict students' scientific issue fathoming capacities utilizing the Bunch Examination (GI) agreeable learning demonstrate instead of routine learning. This inquire about employments a quantitative approach with exploratory strategies and employments a Posttest-Only-Control Plan investigate plan. Course The exploratory lesson test in this inquire about was course X TKJ 1 understudies utilizing the Bunch Examination (GI) learning show whereas the control lesson test X TBSM 3 connected the ordinary learning demonstrate. Information collection procedures and information investigation strategies were carried out utilizing tests and t-tests. Based on information investigation, the normal score for the test lesson understudies was 32.65 and the normal score for the control course was 27.77. So from the comes about of theory testing, tcount is more noteworthy than ttable, specifically 2.1662 > 1.6838, categorized as a centrality of 0.05, so H0 is rejected and H1 is acknowledged. So it can be concluded that the capacity to fathom numerical issues utilizing the Gather Examination (GI) sort agreeable learning demonstrate is way better than utilizing the customary learning show for lesson X understudies at SMKN 10 Merangin for the 2023/2024 scholastic year.